Builders of the vision software and the imagination of design - Cardoso Llach, Daniel (Routledge, 2015)
Builders of the Vision traces the intellectual history and contemporary practices of Computer-Aided Design since the years following World War II until today. Drawing from primary archival and ethnographic sources, it identifies the crucial moments shaping digital design technologies since the first numerical control and CAD systems were developed under US Air Force research contracts at MIT between 1949 and 1970: the cybernetic theorization of design as a human-machine endeavor; the vision of computers as "perfect slaves" taking care of the drudgery of physical labor; the techno-social utopias of computers as vehicles of democracy and social change; the entrepreneurial urge towards design and construction integration; and the managerial ideologies enabling today's transnational geographies of practice. Examining the contrasting, and often conflicting, sensibilities that converge into CAD and BIM discourses--globalism, utopianism, entrepreneurialism, and architects' desires for aesthetic liberation--Builders of the Vision argues that software systems and numerically controlled machines are not merely "instruments," or "tools," but rather versatile metaphors reconfiguring conceptions of design, materiality, work, and what it means to be creative. Crucially, by revealing software systems as socio-technical infrastructures that mediate the production of our built environments, author Daniel Cardoso Llach builds a strong case for the fields of architecture, media, and science and technology studies to critically engage with both the politics and the poetics of technology in design.